RISK FACTORS FOR FETAL GROWTH RETARDATION - Кравченко, Елена Николаевна; Куклина, Лариса Владимировна; Кривчик, Галина Владимировна (Mother and Baby in Kuzbass, 2020)
The aim of the research. Identify the main risk factors affecting the formation of fetal growth retardation (FGR).Material and methods. A retrospective cohort study of 263 birth histories for 2019 was conducted on the basis of the City Clinical Perinatal Center BUZOO in Omsk. The main group consisted of 148 women who gave birth to children with an established diagnosis of FGR. This group was divided into 2 subgroups: the main 1 – 82 women with full-term pregnancy; the main 2 – 66 pregnant women with preterm birth (PB). The control group consisted of 115 women whose urgent delivery ended in the birth of a full-term baby with normal body weight.Results. FGR is more often formed in women with adverse socio-economic factors (working in industries associated with severe physical exertion, living in an uncomfortable environment with harmful effects, with a low economic status, experiencing psycho-emotional stress, and familiar chronic intoxications). Also, FGR was more often detected in pregnant women with a burdened obstetric history (spontaneous miscarriages, preeclampsia, PB, intrahepatic cholestasis), with infectious diseases (with full-term pregnancy in 19.5 %, with PB in 21.2 %); cardiovascular diseases were more common in patients with FGR and PB (39.4 %). In the structure of gynecological diseases in the history of pregnant women with FGR, bacterial vaginitis was in the lead (19.5 % in full-term pregnancy, 27.3 % in PB). In second place, women with PB had uterine fibroids.Conclusion. Among the complications of pregnancy in women with FGR, edema and hypertensive disorders, which threatened spontaneous miscarriage, were more often diagnosed. In the group of women with preterm birth, placental disorders, congenital infection and gestational diabetes were leading.
Keywords: fetal growth retardation